Space Telescopes and Instrumentation 2022: Ultraviolet to Gamma Ray 2022
DOI: 10.1117/12.2630775
|View full text |Cite
|
Sign up to set email alerts
|

The development of the mirror for the Athena X-ray mission

Abstract: Athena is the European Space Agency's next flagship X-ray telescope, scheduled for launch in the 2030s. Its 2.5-m diameter mirror will be segmented and comprise more than 600 individual Silicon Pore Optics (SPO) grazing-incidenceangle imagers, called mirror modules. Arranged in concentric annuli and following a Wolter-Schwartzschild design, the mirror modules are made of several tens of primary-secondary mirror pairs, each mirror made of mono-crystalline silicon, coated to increase the collective area of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This ambitious target is being reached using the technology of Silicon Pore Optics (SPO) under development at ESA and cosine, which will enable to manufacture modular elements (mirror modules, MMs) of densely-nested focusing optics with very low mass-to-effective area ratio and high stiffness. [2] The latest ATHENA design foresees the co-focal integration of 600 MMs into the mirror assembly (MA): each of them needs to be tested, measuring its Point Spread Function (PSF) and its Effective Area (EA) directly in X-rays, prior to integration with a common focus. [3] In order to keep up with the expected production rate of 2 MM/day, an appropriate X-ray test facility shall generate a broad and parallel beam, at the same time avoiding the need of evacuating large volumes, thereby minimizing the time required for MM replacement.…”
Section: The Beatrix X-ray Facilitymentioning
confidence: 99%
“…This ambitious target is being reached using the technology of Silicon Pore Optics (SPO) under development at ESA and cosine, which will enable to manufacture modular elements (mirror modules, MMs) of densely-nested focusing optics with very low mass-to-effective area ratio and high stiffness. [2] The latest ATHENA design foresees the co-focal integration of 600 MMs into the mirror assembly (MA): each of them needs to be tested, measuring its Point Spread Function (PSF) and its Effective Area (EA) directly in X-rays, prior to integration with a common focus. [3] In order to keep up with the expected production rate of 2 MM/day, an appropriate X-ray test facility shall generate a broad and parallel beam, at the same time avoiding the need of evacuating large volumes, thereby minimizing the time required for MM replacement.…”
Section: The Beatrix X-ray Facilitymentioning
confidence: 99%
“…Silicon Pore Optics (SPO) technology has been adopted to produce the NewATHENA X-ray optics. It has been shown that this method can reach the requirements for both Effective Area and HEW [3], remaining within the mass allocated 1 corresponding author: bianca.salmaso@inaf.it; phone +39-02-72320-428; www.brera.inaf.it for the optics. The optics will be built with a modular concept, integrating many Mirror Modules (MM) (492 for NewAthena), each of them based on a stack of several confocal Wolter I shell segments.…”
Section: Introductionmentioning
confidence: 96%
“…To produce the mirrors, commercial 300 mm double-sided super-polished silicon wafers are diced, ribbed and wedged to create rectangular plates with ribs on the bottom side (Collon et al, 2022). Mirror stacks with up to 38 plates are assembled by a stacking robot at the Dutch company cosine so that pores of about 1 mm � 1 mm are formed.…”
Section: Introductionmentioning
confidence: 99%